RESPON PEMUDA TERHADAP NILAI KARAKTER PENDIDIKAN AGAMA ISLAM DI DALAM KELUARGA DAN MASYARAKAT - Lutfi Istighfarinda (Al Ghazali, 2021)
This study aims to analyze youth responses to the character values ​​of Islamic religious education in the family and community in the village of Bendosari, Kebumen, Banyubiru Subdistrict, Semarang Regency. The values of character is very important for the development of children and adolescents due to good character will not only bring a positive influence to the youth itself but also would bring a positive impact on the family, community and environment. This study uses a qualitative approach, the method of data collection is done by in-depth interviews, observation and documentation. The results of this study indicate that in the form of ideas, messages and refraction. The stimulus in the form of ideas and messages is packaged through religious activities such as recitation, tadarus, meetings of youth clubs. The stimulus in the form of habitpuation is packaged in the form of activities such as youth youthfulness, social activities and forth. The response of the youth to the character values ​​of Islamic religious education is in the form of cognitive, affective and psychomotor responses. Cognitive response is a response in the form of ideas and knowledge, affective response is a response in the form of attitudes and emotions while psychomotor responses are responses in the form of behavior or attitude. While the implications of the youth response to the character values ​​of Islamic religious education are in the form of implications in the form of ideas where the ideas and knowledge of youth are getting better and also the implications in the form of attitudes which means that the attitudes and behavior of young people are increasingly changing towards a better direction.